Composition and dynamic of litterfalls of evergreen broad-leaved forest in Baishanzu Mountain, Zhejiang - HU Ling-zhi; CHEN De-liang; ZHU Hui-ling; ZHANG Yong-hua; DING Bing-yang (浙江大学学报. 农业与生命科学版)
The litterfalls of evergreen broad-leaved forest in Baishanzu Mountain were collected by seed rain collector, and they were classified, identified and weighed. The litterfall composition and the monthly dynamics of leaf litter in the forest were also analyzed. The results show that: 1) The amount of the litterfall in the forest was 4 247.47 kg·hm-2·a-1, with leaf litterfall of 71.54% (evergreen leaf litterfall of 51.34%, deciduous leaf litterfall of 20.20%), tree bark and branches of 3.17%, reproductive organs of 19.29%, debris of 6.00%, respectively; 2) The nine dominant species of litterfall had a clear leaf litter dynamics, and the evergreen trees could be classified into three types as follows: the deciduous trees had a peak of leaf litterfall in the autumn and winter, and the evergreen trees had a peak of leaf litterfall in the summer, and the evergreen trees had a peak of leaf litterfall in the summer, autumn and winter; 3) Compared with those of evergreen broad-leaved forest located at the similar latitude, the litterfalls of the Baishanzu Mountain forest were much less, which was a composite reflection for the certain zones of the environment; 4) Flowering and fruiting had a great effect on the dynamics of the litterfalls. Besides, typhoon played an important role on them.